2014
DOI: 10.1002/ange.201405957
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Structural Rearrangements upon Reduction of 9H‐9‐Borafluorene

Abstract: Common wisdom has it that organoboranes are readily oxidized. Described herein is that also their reduction can result in remarkable chemistry. Treatment of dimeric 9H-9borafluorene with Li metal in toluene yields two strikingly different classes of compounds. One part of the sample reacts in a way similar to B 2 H 6 , thus affording an aryl(hydro)borane cluster reminiscent of the [B 3 H 8 ] À anion. The other part furnishes a dianionic boron-doped graphene flake devoid of hydrogen substituents at the boron ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…19− 7.13 (m, 1H), 7.08−7.02 (m, 1H), 6.97−6.92 (m, 1H), 6.88 (t, J = 6.0 Hz, 1H), 6.83 (t, J = 6.0 Hz, 1H), 6.75 (d, J = 12.0 Hz, 1H), 6.72−6.65 (m, 2H); 13 C{ 1 H} NMR (151 MHz, CDCl 3 ) δ 146. 81, 146.40, 145.00, 144.81, 141.70, 136.45, 135.68, 131.62, 131.26, 130.29, 129.92, 129.53, 128.92, 128.72, 128.47, 128.24, 127.86, 127.68, 127.62, 127.32, 127.24, 126.75, 126.62, 126.57, 125.74, 87.01; 11 B{ 1 H} NMR (193 MHz, CDCl 3 ) δ 45.5; FT-IR (cm −1 (ranked intensity)): 1595 (10), 1489 (14), 1439 (5), 1331 (7), 1265 (4), 989 (6), 947 (12), 910 (9), 766 (8), 740 (3), 697 (1), 647 (2), 592 (11), 535 (13), 503 (15); high-resolution mass spectroscopy (HRMS) electrospray ionization (ESI) calcd for C 31 H 23 BONa [M + Na] + 445.1739, found 445.1731; UV−vis (CH 2 Cl 2 ) λ max (235 nm) ε = 6,700 L mol −1 cm −1 ; fluorescence (CH 2 Cl 2 ) λ em 344 nm.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations
“…19− 7.13 (m, 1H), 7.08−7.02 (m, 1H), 6.97−6.92 (m, 1H), 6.88 (t, J = 6.0 Hz, 1H), 6.83 (t, J = 6.0 Hz, 1H), 6.75 (d, J = 12.0 Hz, 1H), 6.72−6.65 (m, 2H); 13 C{ 1 H} NMR (151 MHz, CDCl 3 ) δ 146. 81, 146.40, 145.00, 144.81, 141.70, 136.45, 135.68, 131.62, 131.26, 130.29, 129.92, 129.53, 128.92, 128.72, 128.47, 128.24, 127.86, 127.68, 127.62, 127.32, 127.24, 126.75, 126.62, 126.57, 125.74, 87.01; 11 B{ 1 H} NMR (193 MHz, CDCl 3 ) δ 45.5; FT-IR (cm −1 (ranked intensity)): 1595 (10), 1489 (14), 1439 (5), 1331 (7), 1265 (4), 989 (6), 947 (12), 910 (9), 766 (8), 740 (3), 697 (1), 647 (2), 592 (11), 535 (13), 503 (15); high-resolution mass spectroscopy (HRMS) electrospray ionization (ESI) calcd for C 31 H 23 BONa [M + Na] + 445.1739, found 445.1731; UV−vis (CH 2 Cl 2 ) λ max (235 nm) ε = 6,700 L mol −1 cm −1 ; fluorescence (CH 2 Cl 2 ) λ em 344 nm.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…3H),3H),7.40 (d,J = 8.0 Hz,2H),2H),5H), 7.16 (t, J = 8.0 Hz, 1H), 7.08 (d, J = 8.0 Hz, 1H), 7.04−6.97 (m, 1H), 6.94 (t, J = 4.0 Hz, 3H), 6.77−6.70 (m, 2H); 13 C{ 1 H} NMR (101 MHz, CDCl 3 ) δ 148. 17, 145.94, 141.42, 140.34, 139.49, 139.05, 137.25, 136.55, 131.49, 131.21, 130.82, 130.57, 128.98, 128.87, 127.93, 127.75, 127.73, 127.44, 127.10, 127.00, 126.55; 11 B{ 1 H} NMR (128 MHz, CDCl 3 ) δ 45.6; FT-IR (cm −1 (ranked intensity)) 2095 (4), 1594 (6), 1493 (10), 1436 (5), 1275 (2), 1184 (15), 1130 (12), 1028 (11), 910 (9), 739 (3), 694 (1), 647 (8), 603 (7), 511 (14), 481 (13); high-resolution mass spectroscopy (HRMS) electrospray ionization (ESI) calcd for C 32 H 24 BO [M + H] + 435.1920, found 435.1914; UV−vis (CH 2 Cl 2 ) λ max (234 nm) ε = 35200 L mol −1 cm −1 ; fluorescence (CH 2 Cl 2 ) λ em 351 nm.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Wagner and coworkers then showed that such monoanions, C, (and indeed their diborane(6) precursors) can be reduced to dianionic diborenes [B2R4] 2-(D) by using alkali metals to isolate a biphenylene-bridged diborene. [17][18][19] The inherent electron deficiency of boron in diboron compounds can also be satiated by neutral Lewis bases. For example, neutral diborenes of the form L(R)B=B(R)L (I) are now accessible with a wide variety of bases and covalent substituents via Wurtz coupling of dihaloboranes or reduction of dihalodiboranes.…”
Section: Introductionmentioning
confidence: 99%